SECULAR BEHAVIOR IN THE GEOMAGNETIC DATA AT PERMANENTOBSERVATORIES IN ARGENTINA - P. A. Sallago (Anales AFA, 2024)
The secular variation of the geomagnetic field is the temporal variation that takes place in the field on time scales between few years to hundreds or thousands of years. On the other hand, impulses or ”geomagnetic jerks” indicate a rapid change in the slope of the secular variation. The origin of these phenomena is linked to the behavior of the geodynamo and the contribution of the outer mantle-core interaction.ROMP (acronym from spanish “ Red de Observatorios Magnéticos Permanentes”) is composed by the following observatories: ”Las Acacias ”(LAS) at Buenos Aires,” Trelew ”(TRW) at Chubut,” Pilar ”(PIL) at Córdoba and ”Orcadas”(ORC) at the Argentine sector in Antartic; the first two depend on the National University of La Plata and the latter on the National Meteorological Service. In the present work one analyzes the secular variation and the determination of jerks in the geomagnetic elements recorded at the ROMP stations, in historical times up to the present.